Availability Analysis of Polytube Industry When Two Sub-System Are Simultaneous Fail (Bangladesh Journal of Scientific and Industrial Research, 2012)
The paper discusses the availability of a pipe manufacturing industry using supplementary variable technique. The plant is divided into many sections like mixture, extruder, die and cutter. The failure rates of the sub-systems are constant and the repair rates are general and variable. The mathematical equations are derived using Chapman-Kolmogorov equation. The problem is formulated using the supplementary variable technique and the solution is carried out using the Lagrange's partial differential. Long run availability of the system is also calculated for the various cases using constant transition rates. Key Words: MATLAB; Availability; Chapman-Kolmogorov equation; Lagrange's partial differential. DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9594 BJSIR 2011; 46(4): 475-480